Performance Comparison of Holt-Winters and SARIMA Models forTourism Forecasting in Turkey - (:unkn) unknown (My University, 2020)
Forecasting the number of tourists coming to Turkey can play a vital rolein strategic planning for both private and public sectors. In this study, monthly data offoreigners visiting Turkey were collected between the years 2007 and 2018. The datashowed a seasonal behavior with an increasing trend; consequently, two methods werechosen for the study: Holt-Winters (HW) and Seasonal Autoregressive Integrated MovingAverage (SARIMA). The objective of the study is to determine the most appropriateforecasting model to achieve a good level of forecasting accuracy. The findings showedthat all models provided accurate forecast values according to error measures. However,multiplicative model of HW achieved the highest forecasting accuracy followed bySARIMA and additive HW respectively.

Türkiye’ye gelen turist sayısını tahmin etmek hem özel sektör hem de kamu sektörü için stratejik planlamada çok önemli bir rol oynayabilir. Bu çalışmada, Türkiye’yi ziyaret eden yabancıların sayısı 2007 ve 2018 yılları arasında aylık olarak alınmıştır. Veri artan bir eğilim ile mevsimsel davranış göstermektedir, bu nedenle çalışma için iki metot seçilmiştir: Holt-Winters (HW) and Seasonal Autoregressive Integrated Moving Average (SARIMA). Çalışmanın amacı iyi bir seviyede tahmin doğruluğu elde etmek için en uygun tahmin modelini belirlemektir. Sonuçlar bütün modellerin hata ölçümlerine göre doğru tahmin değerleri verdiğini göstermiştir. Bununla birlikte, HW çarpımsal modeli en yüksek tahmin doğruluğuna erişmiş, bunu sırasıyla SARIMA ve HW toplamsal modeli takip etmiştir.
Türkiye’de Turizm Tahmini İçin Holt-Winters ve SARIMA Modellerinin Performanslarının Karşılaştırılması